2022
DOI: 10.1097/md.0000000000030135
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in repeat-year experience, clinical clerkship performance, and related examinations in Japanese medical students

Abstract: While the number of female medical students is increasing in Japan, gender differences in medical school performance have not been studied extensively. This study aimed to compare gender differences in repeat-year experience, Clinical Clerkship (CC) performance, and related examinations in Japanese medical students. We retrospectively analyzed the number of repeat-year students and years to graduation for male and female medical students, and assessed gender differences in performance on computer-based testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…This is also in line with Brand et al, who showed that females scored signi cantly higher than males among 3rd dental students (11). Gorth et al published that women receive higher scores in the majority of clinical performance (32), and Komasawa et al found signi cantly higher scores and performance in integrative tests and clinical clerkships of female compared to male students (33). Of note, there are also controversial published data showing no difference in academic performance between female and male medical students (34).…”
Section: Discussionsupporting
confidence: 84%
“…This is also in line with Brand et al, who showed that females scored signi cantly higher than males among 3rd dental students (11). Gorth et al published that women receive higher scores in the majority of clinical performance (32), and Komasawa et al found signi cantly higher scores and performance in integrative tests and clinical clerkships of female compared to male students (33). Of note, there are also controversial published data showing no difference in academic performance between female and male medical students (34).…”
Section: Discussionsupporting
confidence: 84%
“…This study population included no minors, as all 4 to 6th year medical students in Japan are >21 years old. [ 10 , 11 ]…”
Section: Methodsmentioning
confidence: 99%
“…This assessment comprises a 5-point evaluation sheet for 16 parts (80%), a subjective evaluation by the organizer of each department (10%), and a written report (10%). [ 10 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations